Radiomics in stratification of pancreatic cystic lesions: Machine learning in action. (28th January 2020) - Dalal, Vipin; Carmicheal, Joseph; Dhaliwal, Amaninder; Jain, Maneesh; Kaur, Sukhwinder; Batra, Surinder K.
Abstract: Pancreatic cystic lesions (PCLs) are well-known precursors of pancreatic cancer. Their diagnosis can be challenging as their behavior varies from benign to malignant disease. Precise and timely management of malignant pancreatic cysts might prevent transformation to pancreatic cancer. However, the current consensus guidelines, which rely on standard imaging features to predict cyst malignancy potential, are conflicting and unclear. This has led to an increased interest in radiomics, a high-throughput extraction of comprehensible data from standard of care images. Radiomics can be used as a diagnostic and prognostic tool in personalized medicine. It utilizes quantitative image analysis to extract features in conjunction with machine learning and artificial intelligence (AI) methods like support vector machines, random forest, and convolutional neural network for feature selection and classification. Selected features can then serve as imaging biomarkers to predict high-risk PCLs. Radiomics studies conducted heretofore on PCLs have shown promising results. This cost-effective approach would help us to differentiate benign PCLs from malignant ones and potentially guide clinical decision-making leading to better utilization of healthcare resources. In this review, we discuss the process of radiomics, its myriad applications such as diagnosis, prognosis, and prediction of therapy response. We also discuss the outcomes of studies involving radiomic analysis of PCLs and pancreatic cancer, and challenges associated with this novel field along with possible solutions. Although these studies highlight the potential benefit of radiomics in the prevention and optimal treatment of pancreatic cancer, further studies are warranted before incorporating radiomics into the clinical decision support system. Highlights: Pancreatic cystic lesions (PCLs) are well known radiographic identifiable precursors of pancreatic ductal adenocarcinoma. Precise and timely management of malignant pancreatic cysts might prevent transformation to pancreatic cancer. Radiomics can be used as a diagnostic and decision making tool to differentiate benign PCLs from malignant ones. We review the radiomics studies done in PCLs, challenges associated with radiomics along with possible solutions.